The immune checkpoint, HVEM may contribute to immune escape in non-small cell lung cancer lacking PD-L1 expression. (November 2018) - Ren, Shengxiang; Tian, Qinrui; Amar, Nadav; Yu, Hui; Rivard, Christopher J.; Caldwell, Charles; Ng, Terry L.; Tu, Megan; Liu, Yiwei; Gao, Dexiang; Ellison, Kim; Suda, Kenichi; et al.
Highlights: HVEM was overexpressed in patients with advanced disease or N2 lymph node metastasis. HVEM expression has a negative co-relationship with PD-L1 expression. HVEM may be a potential target for future immunotherapy. Abstract: Background: : Herpes Virus Entry Mediator (HVEM) is an important immune checkpoint in cancer recognition. HVEM expressed on tumor cell membranes activates immune cell signaling pathways leading to either inhibition of activity (B- and T-lymphocyte attenuator, BTLA) or activation of immune activity (LIGHT). The aim of this study is to investigate the prevalence of HVEM expression and its association with PDL1 expression in NSCLC. Methods: : A TMA of 527 resected NSCLC samples and 56 NSCLC cell lines were evaluated for HVEM and PD-L1 expression. The IHC assay for HVEM was optimized on the Dako Link48 autostainer using a polyclonal antibody from R&D Systems(AF356). PD-L1 IHC was performed on the Dako Link48 autostainer using the PD-L1 28-8 pharmDx kit. Scoring HVEM employed the H-score system while for PD-L1 the tumor proportion score (TPS) was used. Results: : HVEM expression in the NSCLC resected samples and cell lines revealed a positive H-score more than 1 was 18.6% (77/415) and 48.2% (27/56) respectively. HVEM expression was significantly higher in patients with lymph node N2 metastasis (25.5% vs 7.9% vs 17.5%, p = 0.046) when comparing with N1 or no lymph node metastasis, and was marginally significantly higher in patients with stage III/IV disease (24.5% vs 16.4%, p = 0.059). Subgroup analysis showed that HVEM (median 45 vs 36 months, p = 0.706) and PD-L1 expression (median 45 vs 48 months, p = 0.178) status was not predictive of overall survival. HVEM was found to have a significant negative correlation with PD-L1 expression (r=−0.274, p < 0.001) in patients with NSCLC and also a weak negative correlation in NSCLC cell lines (r=−0.162, p = 0.352). Conclusion: : HVEM was found to be overexpressed in NSCLC patients of N2 lymph node metastasis or later stage and has a negative co-relationship with PD-L1 expression. HVEM was not prognostic for NSCLC patients.